Asymmetric Information and Middleman Margins : An Experiment with Indian Potato Farmers - Mitra, Sandip (The MIT Press, 2018)
West Bengal potato farmers cannot directly access wholesale markets and do not knowwholesale prices. Local middlemen earn large margins; pass-through from wholesale to farmgate prices is negligible. When we informed farmers in randomly chosen villages about wholesale prices, average farmgate sales and prices were unaffected, but pass-through to farmgate prices increased. These results can be explained by a model where farmers bargain ex post with village middlemen, with the outside option of selling to middlemen outside the village. They are inconsistent with standard oligopolistic models of pass-through, search frictions, or risk-sharing contracts.